Debt, Current Account, Intellectual Property and FDI: Evidence from 148 Countries - Paul, Sujan Chandra; Rosid, Md. Harun-Or; Begum, Fahmida; Hossain, Shahadat (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2026)
This study aims to explore the effect of foreign direct investment on debt, current account balance and charge for the use of intellectual property. For this, panel data of 148 countries was accumulated for the time frame of 1991 to 2018. This paper employed the OLS, POLS, DK, 2SLS, and GMM models. The study reveals that there is a favorable association between foreign direct investment and external debt stock and receipt of charge for the use of intellectual property and an unfavorable association between FDI and current account balance in all the models used in the study. Payment of charge for the use of intellectual property has significant positive association with foreign direct investment in all models except GMM model. Central government debt has significant negative association in respect of foreign direct investment in POLS models. Revenue has significant positive association with foreign direct investment in OLS and 2SLS model. Short-term debt and foreign direct investment has significant inverse relationship in POLS and GMM model.